1946
DOI: 10.1021/ie50438a028
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Cottonseed and Peanut Oil

Abstract: Study of the effect of heat on cottonseed oil miscella in a practical approach to the problem of objectionable color fixation during heating and solvent removal operations in the solvent extraction process. Heating of cottonseed oil miscellas at various temperatures and definite time periods under appropriate reduced pressures was carried out to determine the effect of heat on the resulting refined and bleached oils. Color fixation became objectionable between 150°and 180°F., and beyond 180°increased rapidly.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1947
1947
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…In order to achieve acceptable color (2.5-6 R) in refined, bleached and deodorized products, hexane-extracted oil required 0.2 to 0.5% excess of 10% lye, whereas the CO2 oil required only 0.1-0.2% excess of the same lye. Processing of crude cottonseed oil presents a problem known as color fixation (9,10). Solvent-extracted and expeller-pressed oils contain appreciable amounts of pigments that, upon heating, become difficult or impossible to remove by refining and/or bleaching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve acceptable color (2.5-6 R) in refined, bleached and deodorized products, hexane-extracted oil required 0.2 to 0.5% excess of 10% lye, whereas the CO2 oil required only 0.1-0.2% excess of the same lye. Processing of crude cottonseed oil presents a problem known as color fixation (9,10). Solvent-extracted and expeller-pressed oils contain appreciable amounts of pigments that, upon heating, become difficult or impossible to remove by refining and/or bleaching.…”
Section: Resultsmentioning
confidence: 99%
“…The raw germ was dried in a forced air draft oven at 27 C until a moisture level of 13% was achieved. Organoleptic evaluations were conducted according to Moser et al (10,11). Representative samples of crude wet-and drymilled corn oils were obtained from commercial sources.…”
Section: Expe R Imentalmentioning
confidence: 99%
“…Besides, processing of cottonseed oil presents a problem known as colour fixation. Solvent-extracted and expellerpressed oils contain appreciable amounts of pigments that, upon heating, become difficult or impossible to remove by even refining/and or bleaching (List, Friedrich, & Pominski, 1984;Vix, Pollard, Spadaro, & Gastrock, 1946).…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus used for steam stripping the remaining solvent from the concentrated miscella and its operation are described in detail in a previous publication (5). The apparatus used for steam stripping the remaining solvent from the concentrated miscella and its operation are described in detail in a previous publication (5).…”
Section: Extractionmentioning
confidence: 99%
“…[previous work (5) having shown that color fixation of miscellas occurred at temperatures above 150~ The colors of the refined and bleached oils obtained were determined by the L0vibond calorimeter.…”
mentioning
confidence: 99%